A service evaluation of Zio XT: the Liverpool experience. Issue 4 (22nd December 2022) - Fawzy, A M; Edmonds, J; Shannon, A; Wright, D J
Abstract: Introduction: The Zio XT is an adhesive, ambulatory heart rhythm monitoring device that can be worn for up to 14 days. It can be fitted by patients and utilises an Artificial Intelligence-based algorithm for rhythm analysis, offering potential convenience, accuracy and efficiency compared to Holter monitors. However, there is a lack of data regarding its efficacy and long-term impact. Thus, until further evidence ensues, NICE guidelines recommend Zio XT as a potential option for those requiring prolonged rhythm monitoring. Purpose: We evaluated the efficacy of Zio XT for heart rhythm monitoring compared to Holter monitors. Methods: 200 sequential patients that had Holter monitors and 204 that had Zio XT were included. Zio cases were randomly selected over 6 months to avoid the learning curve effect. Primary outcomes included time to results and the arrhythmia detection rate. Secondary outcomes included the proportion of patients that had heart rhythm monitoring in the 12 months preceding their investigation, those who required further tests as well as rates of outpatient appointments (OPAs) for device fitting and follow-up, and procedures such as device implantation and ablations. Results: Data from 22 (10.8%) Zio patches was unavailable due to these being lost/not returned/unwearable, thus post-investigation outcomes were analysed for 182 Zio and 200 Holter cases. Zio XT was associated with a significantly shorter time to results compared to Holter monitors (median time: 21 days (interquartile range (IQR) 18–25) vs. 46 days (IQR 37.3–87.8), p<0.001), and a higher significant arrhythmia detection rate (55.4% vs. 17.5%, p<0.001). 26.5% of Zio patients had heart-rhythm monitoring in the preceding 12 months, compared to the 14.5% in the Holter group, p=0.003, with 55.8% having Holters and 28.8% having Zios previously, in the Zio group. A higher proportion of Zio recipients also required repeat tests (19.4 vs. 8.5%, p=0.002). Reasons for this included post-intervention monitoring (44.1%), lack of results due to devices being lost/faulty/not returned (41.2%) and a lack of diagnosis (14.7%). Zio monitoring was associated with a significant reduction in the need for OPAs for fitting (0.5% vs. 96%, p<0.001) and follow-up (70.1% vs. 87.0, p<0.001), and resulted in a significant increase in ablations (5.9% vs. 1.0%, p=0.005) but not device implantations (5.9% vs. 3.9, p=0.209). Conclusion: Our findings indicate that Zio XT is associated with a statistically significant reduction in time to results, higher arrhythmia detection rate and a reduced need for OPAs. We demonstrated a higher rate of both Holter and Zio testing before and Zio testing after these investigations. We postulate that this has partly been due to a learning curve effect with the introduction of a new technology compared to the Holter which has been in use for many decades. Further large-scale evaluation is recommended to yield vital information on management pathways and cost efficacy. Funding Acknowledgement: Type of funding sources: None.